ANALISIS KELAYAKAN USAHATANI IKAN MAS DI DESA BELAMBANGAN KECAMATAN PENGANDONAN KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
This study aims to calculate how much income goldfish farming and feasibility of carp farming in Belambangan Village District Pengandonan OKU. The research method used in the Survey Method. The data method used in this research is with questionnaire as data collection tool. The sampling used in the study was the census method. With a population of 45 peasants and taken as many as 30 people as a sample. The data used is Primary data is data obtained directly from the field by using questionnaires as a means pengmpul data and sekundar data is data obtained from the relevant agencies in this study. Based on the results of research conducted in the Village District Belling Pengandonan Ogan Komering Ulu fish farm income is Rp. 17,863,500 per harvest season. With an average feasibility of 2.89, this means that any expenses earned receive revenue of Rp. 2.89 rupiah during production with a high enough income of Rp. 17,863,500 per harvest season, during Production of Mas Fish Farming.